Effect of cutting parameters on the surface integrity of ground AISI 1148 steel - Ismail, Mohd. Rozaimi (2010)
This work outlines the effect of grinding cutting parameters on the surface integrity namely surface roughness and the surface hardness of AISI 1148 steel during surface grinding. The fundamental concept was that during grinding process, the heat dissipated in the cutting area is used to induce heat treatment of the AISI 1148 steel. ANOVA analysis was then utilized in order to process the data. The cutting parameter involved were work speed, infeed, cross feed and coolant flow rate. The influences of the cutting parameters toward surface roughness and surface hardness had been determined. The data obtain used as input to the statistical analysis software which is Statease.version 8 The ANOVA with full factorial is applied. From the data analysis, it seem that for surface roughness, the most significant cutting parameters were work speed and cross feed. Then for surface hardness, the significant cutting parameters were work speed, cross feed and infeed.